Evaluación Institucional versus Acreditación en la Enseñanza Superior. Implicaciones para la mejora - Mario de Miguel Díaz (Universidad de La Rioja, 2013)
The article approaches the possibilities offered by two methods for evaluation - the "Institutional Evaluation" and the "Accreditation" - considered as tools to promote innovation and the improvement of Higher Education. The author states reasons which allow considering that the models based on processes of self-regulation fit best when promoting improvements as long as they are carried out in a contextualized way and all parts involved participate.